The BBC micro:bit: from the U.K. to the world - Austin, Jonny; Baker, Howard; Ball, Thomas; Devine, James; Finney, Joe; Halleux, Jonathan "Peli" de; Hodges, Steve; Moskal, Michal; Stockdale, Gareth (Communications of the ACM, 2020)
The micro:bit is a small programmable and embeddable computer designed, developed, and deployed by the BBC and 29 project partners to approximately 800,000 U.K. Year 7 (11/12-year-old) school children in 2015–2016. Referring back to its work with the BBC Micro, the BBC described the micro:bit as its “most ambitious education initiative in 30 years, with an ambition to inspire digital creativity and develop a new generation of tech pioneers.” Embracing a constructionist approach to computing education, the micro:bit has moved from a local educational experiment in the U.K. to a global effort driven by the Micro:bit Educational Foundation (microbit.org), a nonprofit organization established in September 2016. There are now over four million micro:bits in the market in over 60 countries with many hardware, content, and education partners participating.